The impact of teacher feedback strategies on writing accuracy among EFL learners - Akhter, Shamim; Kumar, Tribhuwan; Srivastava, Madhurima; Prasad, Rabindra Dev; Borah, Anindita (Research Journal in Advanced Humanities, 2026)
This study investigates the effectiveness of different teacher feedback strategies on improving writing accuracy among English as a Foreign Language (EFL) learners in Pakistani higher education contexts. Writing accuracy remains a critical challenge for Pakistani EFL learners due to limited exposure to English in authentic communicative settings, traditional grammar-translation pedagogies, and insufficient writing instruction. Employing a mixed-methods approach, this research examines three feedback strategies, direct corrective feedback, indirect coded feedback, and metalinguistic feedback applied to 120 undergraduate students across three intact classes at a public sector university in Punjab, Pakistan. Quantitative analysis of pre-test and post-test writing samples measured changes in grammatical accuracy, lexical accuracy, and mechanical accuracy over a 12-week intervention period. Qualitative data from student interviews and teacher reflective journals provided insights into learner perceptions and implementation challenges. Findings reveal that indirect coded feedback produced the most significant improvements in overall writing accuracy (p < 0.001), particularly in grammatical accuracy, while direct corrective feedback showed effectiveness for lower-proficiency learners in mechanical accuracy. Metalinguistic feedback enhanced learners' metalinguistic awareness but required more instructional time. Student interviews revealed preferences for feedback that balanced clarity with cognitive engagement. The study contributes empirical evidence to the ongoing debate about optimal feedback strategies in resource-constrained EFL contexts and offers practical recommendations for Pakistani English language educators seeking to enhance writing instruction through strategic feedback implementation.